In-medium modification of dijets in PbPb collisions at √snn = 5.02 TeV - Sirunyan, A. M. (2021)
Modifications to the distribution of charged particles with respect to high transverse momentum (pT) jets passing through a quark-gluon plasma are explored us ing the CMS detector. Back-to-back dijets are analyzed in lead-lead and proton-proton collisions at √sNN = 5.02 TeV via correlations of charged particles in bins of relative pseu dorapidity and angular distance from the leading and subleading jet axes. In comparing the lead-lead and proton-proton collision results, modifications to the charged-particle relative distance distribution and to the momentum distributions around the jet axis are found to depend on the dijet momentum balance xj , which is the ratio between the subleading and leading jet pT. For events with xj ≈ 1, these modifications are observed for both the leading and subleading jets. However, while subleading jets show significant modifications for events with a larger dijet momentum imbalance, much smaller modifications are found for the leading jets in these events.